Students’ Awareness of Plagiarism in Some Selected Universities in South-western Nigeria - Eka , Njeze Miracle (West African Journal of Open and Flexible Learning, 2017)
This article examined students’ awareness of plagiarism. A survey method was used for this study and the instrument used for collecting data was questionnaire. This study is to ascertain awareness, types, reason for plagiarism in students and existence of plagiarism software/policy in selected universities in Nigeria. Stratified random sampling method was adopted and respondents was selected from faculties of science and social science. Three universities were selected (A, B & C) in south-western, Nigeria. Data was analyzed using frequency counts and simple percent. It was discovered that students from all three universities were aware of plagiarism but still indulge in it by cutting and pasting from the internet. Findings show that plagiarism in university (A) is moderate, but the highest type is the use of articles without proper referencing the author, due to lack of research skills. Data from university B indicates that plagiarism is moderate, but the highest form of plagiarism is the use of a colleague’s work without permission. Data from university C illustrates that plagiarism awareness is high, but the highest form of plagiarism is citing an article in text, without proper referencing of the author. Institutions must ensure that plagiarism is included in their induction programme for students, awareness created on plagiarism, types,policy available in school, and the penalty defined in their hand book on code of ethics. Students must be encouraged to submit their project/thesis electronically in Microsoft word and Turn-it-in” software is recommended for checking articles/research publications. Résumé : Cette recherche examine la conscience des élèves au plagiat. Méthode de recherche par sondage a été utilisée pour cette étude et le questionnaire a été utilisé pour la collecte des données. Cette étude vise à déterminer la sensibilisation, les types, la raison du plagiat chez les étudiants et l’existence d’un logiciel/politique de plagiat dans des universités sélectionnées au Nigeria. Une méthode d’échantillonnage aléatoire stratifié a été adoptée et les répondants ont été choisis dans les facultés des sciences et des sciences sociales. Trois universités ont été sélectionnées (A, B et C) dans le sud-ouest du Nigeria. Les données ont été analysées à l’aide de comptages de fréquence et de pourcentages simples. On a découvert que les étudiants des trois universités étaient conscients du plagiat, mais qu’ils s’y adonnaient encore en coupant et collant de l’Internet. Les résultats montrent que le plagiat à l’université (A) est modéré, mais le type le plus élevé est l’utilisation d’articles sans référence appropriée à l’auteur, en raison du manque de compétences en recherche. Les données de l’université B indiquent que le plagiat est modéré, mais la forme la plus élevée de plagiat est l’utilisation du travail d’un collègue sans permission. Les données de l’université C montrent que la conscience au plagiat est élevée, mais la forme la plus élevée de plagiat est de citer un article dans le texte, sans référence appropriée de l’auteur. Les établissements doivent veiller à ce que le plagiat soit inclus dans leur programme d’initiation des étudiants, à ce qu’une sensibilisation au plagiat, aux types de plagiat, aux politiques disponibles à l’école et aux sanctions définies dans leur manuel d’éthique soit mise en place. Les étudiants doivent être encouragés à soumettre leur projet/thèse par voie électronique en Mot de Microsoft et le logiciel "Turn-it-in" est recommandé pour vérifier les articles/publications de recherche.